Water, Energy, Food, and Ecosystem (W-E-F-E) Nexus River Basin Policy Paradigm for Agriculture Transformation and Multisector Infrastructure Development of Nepal - Upreti, Gopi (Nepal Public Policy Review, 2023)
Water is Nepal’s most abundant resource, and its development and utilization are essential for driving the development of multisector infrastructures (agriculture, energy, industry, urban development, etc.). Nepal has hitherto adopted an isolated and sectoral silo policy approach to development planning that has remained the dominant mode of planning across many countries in the world with few exceptions until recently when inadequacies of sectoral planning became apparent. The search for alternatively more integrative approaches came into the forefront of development discourse in the backdrop of shrinking natural resources, climate change, inexorable demand of a rapidly growing urban population, and other needs and requirements at a global scale. The river basin-wide W-E-F-E nexus development policy strategy offers significant potential for optimum water resource utilization driving development of all sectors, including agriculture. The fundamental aspect of the W-E-F-E nexus policy framework entails the understanding of interdependencies and interactions amidst its components (water, energy, food, and ecosystem) and assessing their synergistic impacts on food, energy, water, and environmental securities in the basin. The W-E-F-E nexus policy framework aims to harness the synergy created from the interaction of interlinked components to achieve sustainable development goals (SDGs). This paper argues that Nepal government must carefully weigh the pros and cons of designing singular run-of-river mega hydro-project visa-vis multipurpose water reservoir projects with provisions of integrating irrigation, drinking water, inland waterways, and flood control infrastructures besides hydro-energy leveraging W-E-F-E nexus relationship.